(untitled) (Faridpur Medical College Journal, 2020)
The existence of subclinical adrenal insufficiency in active tuberculosis is a matter of debate and little is known in this regard. This analytical cross-sectional study is contemplated to find out the association between active tuberculosis and subclinical adrenocortical insufficiency. Where 77 active tubercular patients have been included consecutively in the study along with 30 age and sex matched healthy controls for comparison. Nearly two-thirds (64.9%) of the cases ware diagnosed as pulmonary tuberculosis and rest 35.1% as extra pulmonary tuberculosis. In pulmonary tuberculosis 68.8% had subclinical adrenal insufficiency but 31.2% in extra pulmonary tuberculosis. It shows that 62.3% of the cases had sub-clinical adrenocortical insufficiency as opposed to none in the control group (p < 0.001). Adrenal insufficiency appeared to be significantly associated with smear positivity, X-ray evidence of severe disease and multi-drug resistance. Therefore, physician ought to look for subclinical adrenal insufficiency among patients with active tuberculosis specially if they are sputum positive, X-ray evidence of severe disease and multidrug resistant TB. Faridpur Med. Coll. J. Jul 2019;14(2): 67-70